IMPLEMENTASI PENDIDIKAN KEWARGANEGARAAN DALAM MEMBENTUK WARGA NEGARA YANG TAAT HUKUM - Ubaidillah Al-Ansory Laka; Suherman, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Civics Education (PKn) plays a strategic role in shaping the character of citizens with a strong sense of law-abidingness amidst the dynamics of digital disruption. This study aims to analyze the implementation of the PKn curriculum and the role of the school environment as a social laboratory in internalizing the values ​​of legal compliance in students. The method used was a literature review, synthesizing various scientific sources published between 2021 and 2025. The study's results indicate that legal compliance cannot be formed solely through cognitive mastery of material but requires innovative pedagogical approaches such as Problem-Based Learning and the use of interactive digital media. Furthermore, consistent enforcement of school regulations and exemplary behavior from educators are determining factors in transforming student behavior from mere knowledge to legal awareness. Synergy between schools, families, and law enforcement agencies is essential to creating an educational ecosystem that supports the rule of law. This study concludes that strengthening the adaptive implementation of PKn is a long-term investment for social stability and national resilience.